Feasibility Analysis of Cauliflower Farming (Brassica oleracea var. botrytis L.) in Ciwaringin Village, Lemahabang District, Karawang Regency - Arsi Dwi Rismaya; Abubakar Abubakar; Wagiono Wagiono (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Purpose : The objective of this study is to analyze the feasibility of cauliflower farming in Ciwaringin Village, Lemahabang Subdistrict, Karawang Regency. Methodology: This study uses quantitative descriptive research with a sample of 30 farmers selected through a saturated sampling method. Data analysis was performed using total cost, revenue, income, R/C ratio, and Break Even Point (BEP) analyses. Results: From the analysis of farming data, it was found that on average, the total production costs incurred by farmers were IDR 34,554,170/ha/MT, revenue was IDR 73,965,000/ha/MT, and income was IDR 39,410,830/ha/MT. The R/C ratio was 2.14. Findings: This study found that cauliflower farming in the study location was above the break-even point, with a BEP of Rp 20,444,071/ha/MT, a BEP of 4,103 kg/ha/MT, and a BEP price of Rp 2,336/kg. Novelty: The novelty of this study lies in the comprehensive analysis of the feasibility of cauliflower farming using an integrated BEP approach, which has not been widely applied at the farmer level in the study area. Originality: This research is original because it uses actual data from cauliflower farmers in Ciwaringin Village and provides a realistic picture of the economic conditions of farming that can be used as a reference for cost management and increasing farmer income. Conclusion: Based on the analysis results, cauliflower farming in Ciwaringin Village is feasible to implement and develop. These findings are expected to serve as a basis for farmers in planning their farming activities and for relevant parties in formulating policies for the development of cauliflower as a commodity. Type of Paper : Research article.